Psychotherapeutic interaction in dyad "doctor - patient" in neurological practice - Вірна, Жанна Петрівна; Прус, Оксана Валеріївна (Psychological Counseling and Psychotherapy, 1970)
The article theoretically concretizes the content of psychotherapeutic interaction in dyad «doctor – patient» in practice of neurosology. Argumentation of the problem concerns issues needed to study this aspect because of obligatory determination the efficiency of psychotherapeutic methods for individual clinical neurosis manifestations. It is emphasized that psychogenic origins of neuroses require psychotherapeutic intervention, an indicator of its quality is developed psychotherapeutic style of interaction between doctor and patient.